Penciptaan Busana Ready to Wear dengan Motif Gendang Beleq dan Rumah Bale - Yunika, Anif Fatma; Kusumawardani, Hapsari; Aini, Nurul; Nafiah, Annisau (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Gendang Beleq and Bale Lumbung House are traditional arts and traditional houses that characterise the Sasak Lombok tribe. Gendang Beleq and Bale Lumbung House are used as a source of ideas and realised as digital printing motifs with the intention of preserving and introducing traditional arts and culture in Indonesia. The research results stated: (1) The concept of ready to wear fashion creation combines elements of nature and culture, namely the beauty of Kuta Beach Lombok, the traditional art of Gendang Beleq and the traditional house of the Sasak tribe, namely the Bale Lumbung House. (2) The process of creating the fashion work refers to Hendriyana's Practice-led Research method which consists of four stages, namely Pre-design, Design, Realisation and Presentation of Work. (3) The final result of the work consists of 2 fashion looks that are classified as ready to wear clothing with a loose cut. The first work consists of 5 items, namely outer printing top, plain white culottes made from duchess satin, skirt made from navy duchess satin with additional wide rope ties around the waist with a width of 4 cm, tie printing bodice and white knit inner. The second look consists of 5 items, namely outer printing, printed culottes, obi belt with circular strap with seashell motif printing, printed ikat skirt and white inner knit.